If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7x + 3 = -3x + -11 + 15x Reorder the terms: 5 + 3 + -7x = -3x + -11 + 15x Combine like terms: 5 + 3 = 8 8 + -7x = -3x + -11 + 15x Reorder the terms: 8 + -7x = -11 + -3x + 15x Combine like terms: -3x + 15x = 12x 8 + -7x = -11 + 12x Solving 8 + -7x = -11 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 8 + -7x + -12x = -11 + 12x + -12x Combine like terms: -7x + -12x = -19x 8 + -19x = -11 + 12x + -12x Combine like terms: 12x + -12x = 0 8 + -19x = -11 + 0 8 + -19x = -11 Add '-8' to each side of the equation. 8 + -8 + -19x = -11 + -8 Combine like terms: 8 + -8 = 0 0 + -19x = -11 + -8 -19x = -11 + -8 Combine like terms: -11 + -8 = -19 -19x = -19 Divide each side by '-19'. x = 1 Simplifying x = 1
| 12=10x+4x-16 | | 4/24=16/x | | 60/5=6/x | | 60/5=10/x | | x=1/2y-5 | | 12-4x=10x-16 | | 55/11=5/x | | 50/5=10/x | | 2/5*x=28 | | 7x+14=-15x-6 | | 0.30=log(x) | | 42/7=14/x | | 21x-6-18x+2=17x-8-14x+11 | | 42/7=6/x | | 7/42=6/x | | 3x^9u^2*7u^6*2x= | | 27x^2+3x-10=0 | | 2v^9x^2*3x^7*7v= | | 2.1+3b=1.8 | | 12/24=6/x | | y+50=x | | 16x^2+65.5x+5.5=0 | | 9x-6=8x+11 | | 5p-0.48=0.12 | | 2y-1=5y-10 | | 3/4x4/9 | | h=6+17t-16t+2 | | 7w*2w^8v^4*3v^2= | | 0=91+13t | | x/-6+7=0 | | 3+d/2=10 | | (x-3)/(x^3-9x^2+24x-18) |